Ratio of remnant to total liver volume or remnant to body weight: which one is more predictive on donor outcomes - DEMİRBAŞ, BAHA TOLGA (My University, 2012)
Backround: Right lobe donations are known to expose the donors to more surgical risks than left lobe donations. In the present study, the effects of remnant volume on donor outcomes after right lobe living donor hepatectomies were investigated. Methods: The data on 262 consecutive living liver donors who had undergone a right hepatectomy from January 2004 to June 2011 were retrospectively analysed. The influence of the remnant on the outcomes was investigated according to the two different definitions. These were: (i) the ratio of the remnant liver volume to total liver volume (RLV/TLV) and (ii) the remnant liver volume to donor body weight ratio (RLV/BWR). For RLV/TLV, the effects of having a percentage of 30% or below and for RLV/BWR, the effects of values lower than 0.6 on the results were investigated. Results: Complication and major complication rates were 44.7% and 13.2% for donors with RLV/TLV of 30%, and 35.9% and 9.4% for donors with RLV/BWR of < 0.6, respectively. In donors with RLV/TLV of 30%, RLV/BWR being below or above 0.6 did not influence the results in terms of liver function tests, complications and hospital stay. The main impact on the outcome was posed by RLV/ TLV of 30%. Conclusion: Remnant volume in a right lobe living donor hepatectomy has adverse effects on donor outcomes when RLV/TLV is 30% independent from the rate of RLV/BWR with a cut-off point of 0.6.
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; İç Hastalıkları; Gastroenteroloji-(Hepatoloji); Cerrahi Tıp Bilimleri; Medicine; Health Sciences; Internal Medicine Sciences; Internal Diseases; Gastroenterology and Hepatology; Surgery Medicine Sciences; GASTROENTEROLOJİ VE HEPATOLOJİ; Klinik Tıp; Klinik Tıp (MED); CERRAHİ; GASTROENTEROLOGY & HEPATOLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); SURGERY; Surgery; Gastroenterology; Hepatology; liver transplantation; living donor; remnant; right lobe; donor outcome; body weight; PORTAL-HYPERTENSION; IN-VITRO; TRANSPLANTATION; RESECTION; RECIPIENTS; MORBIDITY; FAILURE; GRAFTS; SAFETY; SIZE; liver transplantation; living donor; remnant; right lobe; donor outcome; body weight